Primary Human Microglia Are Phagocytically Active and Respond to Borrelia burgdorferi With Upregulation of Chemokines and Cytokines - Greenmyer, Jacob R.; Gaultney, Robert A.; Brissette, Catherine A.; Watt, John A. (Frontiers in Microbiology, 2018)
The Lyme disease causing bacterium Borrelia burgdorferi has an affinity for the central nervous system and has been isolated from human cerebral spinal fluid by 18 days following Ixodes scapularis tick bite. Signaling from resident immune cells of the central nervous system (CNS) could enhance CNS penetration by B. burgdorferi and activated immune cells through the blood brain barrier resulting in multiple neurological complications, collectively termed neuroborreliosis. The ensuing symptoms of neurological impairment likely arise from a glial-driven, host inflammatory response to B. burgdorferi. To date however, the mechanism by which the bacterium initiates neuroinflammation leading to neural dysfunction remains unclear. We hypothesized that dead B. burgdorferi and bacterial debris persist in the CNS in spite of antibiotic treatment and contribute to the continuing inflammatory response in the CNS. To test our hypothesis, cultures of primary human microglia were incubated with live, antibiotic-killed and antibiotic-killed sonicated B. burgdorferi to define the response of microglia to different forms of the bacterium. We demonstrate that primary human microglia treated with B. burgdorferi show increased expression of pattern recognition receptors and genes known to be involved with cytoskeletal rearrangement and phagocytosis including MARCO, SCARB1, PLA2, PLD2, CD14 and TLR3. In addition, we observed increased expression and secretion of pro-inflammatory mediators and neurotrophic factors such as IL-6, IL-8, CXCL-1 and CXCL-10. Our data also indicate that B. burgdorferi interacts with the cell surface of primary human microglia and may be internalized following this initial interaction. Furthermore, our results indicate that dead and sonicated forms of B. burgdorferi induce a significantly larger inflammatory response than live bacteria. Our results support out hypothesis and provide evidence that microglia contribute to the damaging inflammatory events associated with neuroborreliosis.